Formation of the systematic mind in the Islamic thought: the case of Ibn Khaldun - Ahmed Shogar, Ibrahim Adam (2014)

(untitled)
The main objective of this paper is to explain meaning and the general characteristic of systematic mind in Islamic thought, with especial reference to Ibn Khaldun’s approach in his “al-Muqaddimah”. The author holds the view that lack of systematic thought was one of the major causes of scientific decline in Islamic civilization. According to modern information science, the progression from ‘data’ to ‘wisdom’ is the framework for systemization of knowledge which enables human intellect to differentiate the various levels of what we see and what we know in the natural world. This systematic investigation constitutes the foundations of scientific method which differentiates between science and other modes of human knowledge. The systematic mind is a mode of thought which inclined to conform with the scientific method; in addition to its substantial capabilities of extracting the general principles and specific conclusions from individual observations. Abstraction, generalization and systemization are the general characteristics of the systematic mind, which can be formed naturally or acquired by means of experience and learning. These characteristics have enabled the human intellect to be the main source of scientific growth throughout the human history. There are many good examples of systematic mind in Islamic thought, but Ibn Khaldun’s approach in his “Al-Muqadimmah” was substantial. This paper aims to explain how Ibn Khaldun was able to develop the systematic mind based on Qur`anic injunctions and guidelines. Along the way, the paper explains the major implications of systematic thinking on revival of the modern Islamic thought and development of Muslim communities.